Case Study on Migrated Women Employment from Rural to Urban Areas in Uttarakhand - Verma , Tulika Uniyal (Gyan Management Journal, 2023)
This case study explores the phenomenon of women’s migration from rural to urban areas in Uttarakhand, India, and its impact on their employment patterns. Uttarakhand, a hilly state located in northern India, has witnessed significant rural-to-urban migration in recent years. The study investigates the socio-economic factors driving this migration, the challenges faced by migrant women in the process, and the opportunities and constraints they encounter in securing employment in urban settings. The research employs a mixed methods approach, combining qualitative interviews and focus group discussions with quantitative analysis of secondary data. Primary data collection involves interviews with migrated women, community leaders, and key stakeholders in urban areas, along with focus groups comprising both migrants and non-migrants. Secondary data sources include government reports, academic studies, and relevant literature. The findings reveal several key insights. Firstly, economic factors, such as lack of employment opportunities, limited agricultural productivity, and aspirations for better livelihoods, emerge as primary motivations for rural women’s migration to urban areas. Secondly, social factors, including changing gender roles, education, and social networks, play a significant role in the decision-making process. However, the study also uncovers numerous challenges faced by migrated women, including discrimination, exploitation, inadequate access to education and healthcare, and limited social support networks. Moreover, the